Improving treatment of substance use disorders through community drug treatment clinics: An experiential account - Ravindra Rao; Anju Dhawan; Arpit Parmar; Deepak Yadav; Roshan Bhad (Wolters Kluwer Medknow Publications, 2021)
India has a huge burden of substance use disorder (SUD). The national response to the problem of SUD has been to support addiction treatment centers either in government hospitals or in nongovernmental settings. The existing number of addiction treatment facilities is less compared to the burden of substance use in India. The existing models of treatment in India place undue emphasis on inpatient treatment of SUD. Community-based treatment aims to bring the treatment of SUD closer to the patients in their community. Community-based treatment of SUD utilizes existing services available in the community by establishing an integrated network of community-based services. There have been different models of community-based care for the management of SUD in India. Most of them, however, address short-term withdrawals and do not provide long-term treatment in community. National Drug Dependence Treatment Centre, AIIMS, New Delhi, has been providing community-based treatment for SUD since the 1990s. Two of the three community drug treatment clinics (CDTCs) are in operation for more than 5 years now and cater to the population residing within a defined catchment area. The CDTCs use infrastructure available in the community to operate the clinics. The clinics are run daily by a team of nursing staff, while the doctor is available only twice a week. A menu of options, ranging from short-term treatment to long-term agonist maintenance treatment is provided in the clinic. Both pharmacotherapy and psychosocial interventions are provided. Each clinic caters to hundreds of patients through these facilities. There is a need to expand CDTCs in India considering their cost-effectiveness, acceptability, and overall effectiveness, especially in urban colonies with higher substance-related problems.